Cluster Analysis of The EU Income Inequalities in The Context of the COVID-19 Effects - Amalia CRISTESCU; Maria Denisa VASILESCU; Larisa STANILA; Eva MILITARU (Communications of International Proceedings, 2022)
As part of the research, we carried out an analysis of a range of indicators specific to education and the labour market, and respectively income inequalities and socio-economic vulnerabilities during the COVID-19 pandemic, aiming to later identify the distribution of the EU states according to these indicators. Also, we were particularly interested in the indicators’ evolutions in Romania given by the persistent high-income inequalities observed in this country. By means of a cluster analysis we tried to identify common elements for the development of appropriate strategies and policies according to the existing nerve points. The resulting groups were quite heterogeneous, an aspect that highlighted the fact that no specific developments for emerging countries or respectively developed countries can be observed. On the contrary, we see that the socio-economic evolution during the COVID-19 period is strongly linked with the pre-existing conditions at the time of the pandemic outbreak. The evidence provided in our article may be useful in identifying the most effective policy path to address inequality at the EU level.
Keywords: income inequality; education; labour market; cluster analysis